2011
DOI: 10.1074/jbc.m111.251884
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Biocompatibility Assessment of Inhaled Single-wall and Multiwall Carbon Nanotubes in BALB/c Mice

Abstract: With the widespread application of carbon nanotubes (CNTs) in diverse commercial processes, scientists are now concerned about the potential health risk of occupational exposures. In this study, CNT-induced pulmonary toxicity was investigated by exposing BALB/c mice to aerosolized single-wall (SW) CNT and multiwall (MW) CNT (5 g/g of mice) for 7 consecutive days in a nose-only exposure system. Microscopic studies showed that inhaled CNTs were homogeneously distributed in the mouse lung. The total number of bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Comparing these studies to the result of the present study, we hypothesize that up-regulation of fibrosis related gene expression observed following CNT Large exposure only, could be due to the structural differences between CNT Large and CNT Small . However, it should be noted that some studies observe no differences in the fibrotic potential between CNTs of different lengths (Muller et al, 2005;Ravichandran et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Comparing these studies to the result of the present study, we hypothesize that up-regulation of fibrosis related gene expression observed following CNT Large exposure only, could be due to the structural differences between CNT Large and CNT Small . However, it should be noted that some studies observe no differences in the fibrotic potential between CNTs of different lengths (Muller et al, 2005;Ravichandran et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…In particular, MWCNTs promote the death of human epithelial cells [42,52,54,76,72], human lymphocytes [43,51], human macrophages [44], human connective tissues [75], human cancer cell lines [89][90][91][92], as well as many animal cell lines. Interestingly, there is also literature claiming the contrary [94][95][96][97][98][99]. This controversy illustrates the huge variability of existing CNTs in terms of lengths, diameters, surface functionalization, contaminants, etc., as well as the diverse nature of the cells used for the different in vitro toxicological assays performed.…”
Section: Mwcnts Are Intrinsically Cytotoxic In a Va-riety Of Cancer Cmentioning
confidence: 91%
“…Nevertheless, MWCNTs are potentially very harmful environmental pollutants because of three major factors: the shape of the particles; their surface reactivity; and their clearance difficulty [9]. To improve the mechanical properties of MWCNTs, sufficient wetting and uniform dispersion in various media, including aqueous solutions, are required [6, 10].…”
Section: Introductionmentioning
confidence: 99%